A Gender Differences in Psychosocial of Adolescent Behavioral and Subtace Addiction: A Comparative Quantitative Study - Mila Yunita; Wiryo Nuryono; Palasara Brahmani Laras; Barbella Khayla Syavanda Saputri (Universitas Negeri Padang, 2026)
Adolescent behavioural and substance-related addictive tendencies have become an increasing concern due to their potential impact on mental well-being and academic performance. However, research on the psychosocial contexts associated with these tendencies has been limited, especially from a gender perspective. This study aimed to investigate gender-related differences in self-reported addiction symptoms and related psychosocial triggers among adolescents. A quantitative comparative design was used, involving 92 high school students in East Java. Data were collected using a self-administered screening questionnaire comprising 12 items across four dimensions: psychological stress, family pressure, social pressure, and social media influence. Descriptive statistics and independent samples t-tests were conducted using SPSS Statistics. Descriptively, participants reported the highest mean media influence scores. Female respondents reported slightly higher mean values on several dimensions; however, no statistically significant gender differences were found in overall addiction symptom scores or across psychosocial trigger dimensions. Effect size estimates indicated small differences between groups. These findings suggest that psychosocial addiction triggers are generally comparable across genders within this sample. The results should be interpreted with caution and are intended to offer descriptive insights rather than causal conclusions. Limitations include reliance on self-reported measures, a modest sample size, and a cross-sectional design. Future research should utilise validated instruments and larger samples to further explore the psychosocial mechanisms underlying adolescent addiction-related behaviours.